Development of Lithium-Stuffed Garnet-Type Oxide Solid Electrolytes with High Ionic Conductivity for Application to All-Solid-State Batteries - Inada, Ryoji; Yasuda, Satoshi; Tojo, Masaru; Tsuritani, Keiji; Tojo, Tomohiro; Sakurai, Yoji (Frontiers in Energy Research, 2016)
All-solid-state lithium-ion battery (LiB) is expected as one of the next generation energy storage devices because of their high energy density, high safety and excellent cycle stability. Although oxide-based solid electrolyte materials have rather lower conductivity and poor deformability than sulfide-based one, they have other advantages such as their chemical stability and easiness for handling. Among the various oxide-based SEs, lithium stuffed garnet-type oxide with the formula of Li7La3Zr2O12 (LLZ) have been widely studied because of their high conductivity above 10-4 Scm-1 at room temperature, excellent thermal performance and stability against Li metal anode.Here, we present our recent progress for the development of garnet-type solid electrolytes with high conductivity by simultaneous substitution of Ta5+ into Zr4+ site and Ba2+ into La3+ site in LLZ. Li+ concentration was fixed to 6.5 per chemical formulae, so that the formulae of our Li garnet-type oxide is expressed as Li6.5La3-xBaxZr1.5-xTa0.5+xO12 (LLBZT) and Ba contents x are changed from 0 to 0.3. As results, all LLBZT samples have cubic garnet structure without containing any secondary phases. The lattice parameters of LLBZT decrease with increasing Ba2+ contents x < 0.10 while increase with x from 0.10 to 0.30, possibly due to the simultaneous change of Ba2+ and Ta5+ substitution levels. Relative densities of LLBZT are in the range between 89% and 93% and not influenced so much by the compositions. From AC impedance spectroscopy measurements, the total (bulk + grain) conductivity at 27ºC of LLBZT shows its maximum value of 8.34 x 10-4 S cm-1 at x = 0.10, which is slightly higher than the conductivity (= 7.94 x 10-4 S cm-1) of LLZT without substituting Ba (x = 0). Activation energy of the conductivity tends to become lower by Ba substation, while excess Ba substitution degrades the conductivity in LLBZT. LLBZT has wide electrochemical potential window of 0-6 V vs. Li+/Li and reversible Li+ insertion and extraction reactions of TiNb2O7 film electrode formed on LLBZT by aerosol deposition are successfully demonstrated at 60ºC. The results indicate that LLBZT can potentially be used as a solid electrolyte in all-solid-state batteries.